PENGARUH STRATEGI PEMBELAJARAN DAN MINAT BERWIRAUSAHA TERHADAP HASIL BELAJAR MENGGAMBAR POLA MODIFIKASI PAKAIAN DAERAH SISWA SMK NEGERI 8 MEDAN - Rosita Carolina (Universitas Negeri Medan, 2014)
ABSTRACT Research aims: (1) differences in learning outcomes Drawing Clothes Pattern Modifications Regional taught by STAD cooperative learning strategies and learning outcomes Drawing Clothes Pattern Modifications Regional expository taught learning strategies; (2) differences in learning outcomes draw the pattern modification Clothing Regions that have a high interest in entrepreneurship that have low interest in entrepreneurship; and (3) the interaction between learning strategy and the learning outcomes of interest in entrepreneurship drawing modification patterns clothing area. Its population is students of class XI as much as 129 people; the sample is a class XI - 1 Clothing 30 people and Clothing - 3 classes XI by 32 people. The instrument used to collect the data is achievement test and questionnaire interest in entrepreneurship. Method using quasi- experimental research design with a 2x2 factorial study a = 0.05 Techniques of data analysis using ANOVA at significance level Results of analysis that: (1) the results of learning to draw patterns clothing modification areas taught by cooperative learning strategy STAD higher than the learning outcomes Regional Clothing Modifications Pattern Drawing taught by teaching expository ( Fvalue = 72.52 > F= 4.10), (2) there are significant differences between learning outcomes Drawing Clothes Pattern Modifications Regions that have a high interest in entrepreneurship with students who have low entrepreneurship interests, (Fvalue=6.63>Ftable= 4.10 ), and 3) there was an interaction between learning strategy and the learning outcomes Interests Entrepreneurship Draw Regional Clothing Pattern Modification (Fvalue = 29.12 > F = 4.10 ). Kata Kunci : Strategi Pembelajaran, Minat Berwirausaha dan Hasil Belajar Menggambar Pola Modifikasi Pakaian Daerah.